Estudio de Dispositivos RFID para el Registro de Existencia de Libros y Control de Bienes en la Biblioteca de la FAFI - Troya Ramirez, Vanessa Tatiana (2018)
The Faculty of Administration Finance and IT FAFI, as well as in many establishments, it is necessary to keep control of inventory and books where it can be the case that there is not sufficient control pending of the study materials, on the other hand also the library can count on a great variety of texts. The inventory constitutes one of the most significant items for the institution that allows having an internal control of the library in order to optimize resources and materials that help improve the attention to users and reduce the risks of loss of books and goods, also minimize human errors so that the information is accurate and timely. In the FAFI library, despite the existence of a Computer System (Ekubiblio) that manages the books and their loans, the registration of these books causes a disorganization and incoordination when it requires detailed information about the books that are available in the library of the institution. For which the library needs to have technological devices that optimize the registration and searches of books. Currently the library does not have technological devices that allow to label the books in a correct way the labeling is elaborated manually due to the inconveniences, at the moment of search of the texts it takes even the books do not have a specific format, some of the problems That there is the agglomeration of student at the time of applying for a loan is to improve your search.